Effects of skin-to-skin care on electrical activity of the diaphragm in preterm infants during neurally adjusted ventilatory assist. (June 2021) - Kato, Yuta; Takemoto, Ayumi; Oumi, Chiyo; Hisaichi, Tomomi; Shimaji, Yuki; Takaoka, Misa; Moriyama, Hiroko; Hirata, Katsuya; Wada, Kazuko
Abstract: Background: Skin-to-skin care (SSC) reduces neonatal mortality and morbidity and is widely implemented in the neonatal intensive care unit. However, changes in respiratory effort during SSC in ventilated preterm infants remain unclear. Aims: To evaluate the effect of SSC on electrical activity of the diaphragm (Edi) and vital signs in premature infants who are intubated and under neurally adjusted ventilatory assist ventilation. Study design: We performed an observational cross-over study. Data were measured in three periods: before (pre-SSC period), during (SSC period), and after (post-SSC period) SSC. Stable 30-min data in each period were extracted. Subjects: Thirty-four SSC procedures were performed in 14 preterm infants with a median gestational age of 25.3 weeks (interquartile range, 24, 26.4) and a birth weight of 659 g (566, 694). The median postnatal age was 41 days (31, 53) at the study with a median postmenstrual age of 31.3 weeks (30.4, 32.5). Outcome measures: Median values of Edi peak, Edi minimum, respiratory rate, SpO2, and heart rate were measured in each condition. The Kruskal–Wallis test with Bonferroni multiple comparisons was used to compare each parameter in each period. Results: Median Edi peak and Edi minimum values were significantly lower during SSC compared with pre- and post-SSC, without any change in respiratory rate, SpO2, or heart rate. Conclusions: Respiratory efforts as evaluated by Edi are significantly reduced during SSC in ventilated preterm infants. Highlights: Edi were evaluated during skin-to-skin care (SSC) in ventilated preterm infants. Respiratory efforts are reduced during SSC. Tonic activities are reduced during SSC.